Personality traits spectrum in panic disorder and major depression - Freire,Rafael C (2007)
OBJECTIVE: Our aim was to identify the personality traits in patients with panics disorder, major depression and with both disorders (comorbidity). METHOD: Diagnoses were made with the Structured Clinical Interview for DSM-IV before the treatment, and the personality evaluation with the Maudsley Personality Inventory was made during the follow-up. Four groups were analyzed: a control group (n = 30), a major depression without panic disorder group (n = 45); a panic disorder without major depression group (n = 56) and a comorbidity group (n = 21), with major depression and panic disorder, simultaneously. RESULTS: All disorder groups had significantly higher neuroticism means when compared to the control group. The highest mean was in the comorbidity group, followed by the major depression group and the panic disorder group. The difference of neuroticism means between the comorbidity group and the panic disorder group also reached statistical significance. The lowest extraversion mean was in the comorbidity group, followed by the major depression group, the panic disorder group, and the control group. Compared to normal controls, extraversion was significantly low in the comorbidity and major depression groups. CONCLUSION: In our sample, there was a continuum of personality traits between panic disorder and major depression and, the co-occurrence of these disorders was associated with accentuated personality traits.